Colloidal Nanoparticles for Heterogeneous Catalysis - Destro, Priscila (Springer Theses, Recognizing Outstanding Ph.D. Research, 2019)
This book explores the formation of colloidal gold-copper (AuCu) alloy nanoparticles and evaluate their application in heterogeneous catalysis. Metal alloys are extremely versatile materials that have been used since the Antiquity to improve the properties of commonly used metals, therefore the understanding of their properties has fostered the applications in areas such as photonics, sensors, clinical diagnostics, and especially in heterogeneous catalysis, which allows catalyst active sites to be modulated. In this book, readers will appreciate the fundamental aspects involved in the synthesis of AuCu nanoalloys, including real-time information about their atomic organization, electronic properties, as well a deeper understand about the behavior of AuCu supported nanoalloys under real catalytic conditions, providing interesting insights about the effect of the support on the nanoalloy stability. The results presented here open new horizons for using metal alloys in catalysis and also other areas where the metal-support interface may play a crucial role.